Perancangan Aplikasi Kuesioner Penilaian Kinerja Dosen pada Universitas Methodist Indonesia Berbasis Website - Marshanda Febyola Rajagukguk; Roni Jhonson Simamora; Rimbun Siringoringo (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The assessment of lecturer performance at Indonesian Methodist University is a crucial component in maintaining and enhancing the quality of education. Manual assessment processes encounter various challenges, including inefficiency, prolonged durations, and the potential for human error. Therefore, a digital solution is necessary to simplify and optimize the assessment process. This research aims to design and develop a web-based lecturer performance assessment questionnaire application that enhances efficiency, accuracy, and ease of use in the assessment process at Indonesian Methodist University. The application design is conducted using the Unified Modeling Language (UML) method, which involves creating use case diagrams, class diagrams, and activity diagrams. This approach facilitates the design of a well-structured and documented system, thereby streamlining the development and implementation processes. The research findings indicate that the questionnaire application designed with UML significantly improves the efficiency and accuracy of the lecturer performance assessment process. Additionally, this application simplifies user access to online questionnaires and generates reliable assessment reports.